Gabriel J. Zanotti, El Humanismo del Futuro, Editorial de }Migran°, Buenos Aires, 1989, 262 pp - Derisi, Octavio Nicolás (1990)
Fil: Derisi, Octavio Nicolás. Pontificia Universidad Católica Argentina; Argentina